Exploring the factors associated with professional and non-professional dancer well-being: a comprehensive systematic review - Yu, Haiyan; Teo, Eng Wah; Tan, Chai Chen; Chang, Jindong; Liu, Shenghui (Frontiers in Psychology, 2025)
BackgroundDance is a physically and psychologically demanding activity that can significantly affect dancers’ overall well-being. While interest in this area has increased, no comprehensive systematic review has synthesized existing findings across diverse populations and contexts. This study addresses this gap by reviewing how dancers’ well-being has been conceptualized and measured, identifying key associated factors, and evaluating available interventions.MethodsFollowing PRISMA guidelines, 18 peer-reviewed studies published from 1984 to November 2024 were included, sourced from Web of Science, Scopus, PubMed, SPORTDiscus, and manual searches. The Mixed Methods Appraisal Tool (MMAT) was used to assess the risk of bias.ResultsThe synthesized evidence reveals a growing trend toward adopting eudaimonic and multidimensional frameworks in the conceptualization of dancer well-being, with the Positive and Negative Affect Schedule being the most frequently employed instrument to measure dancers’ well-being. Dancers’ well-being is significantly associated with multiple factors, including demographic factors, motivational climate, psychological factors, as well as organizational stressors and resources. Notably, only one study employed a randomized controlled trial design.ConclusionThis review also identifies several important areas for future research, including the adoption of longitudinal and mixed-methods designs, the development of validated and dancer-specific measures of well-being, and the design of interventions applicable to dancers across a broader range of dance genres, professional levels, and underrepresented groups, such as male dancers and individuals from diverse cultural contexts. These findings provide an integrated understanding of the key psychological factors, theoretical models, and methodological approaches shaping dancers’ well-being, offering a foundation for future targeted interventions and research.Systematic review registrationCRD420251003173, https://www.crd.york.ac.uk/PROSPERO/view/CRD420251003173.